EFEKTIVITAS PELAYANAN KARANTINA TUMBUHAN PADA UNIT PELAYANAN I DI BALAI KARANTINA PERTANIAN SURABAYA - Nursafitri, Amalia Lusi (FISIP UWP, 2024)
This study address to the effectiveness of plant quarantine services at Service Unit I at the Surabaya Agricultural Quarantine Center, as well as factors that influence and efforts to improve its effectiveness. The following research method is descriptive qualitative. The research subjects being the leadership, service staff and service users of the Surabaya Agricultural Quarantine Center. Sources of information were determined using purposive sampling techniques, data collection techniques through interviews, documentation and literature studies, and data analysis techniques with data collection, data condensation, data presentation, and conclusion drawing. The results showed that: (1) The effectiveness of plant quarantine services tangibles, reliability, responsiveness, assurance, empathy runs quite effectively and efficiently so that service users feel satisfied with the service. (2) Factors that influence, namely awareness factors, regulatory factors, organizational factors, facilities and infrastructure factors, income factors and employee skills factors, carry out their responsibilities to serve the community well, sufficiently apply the rules that have been enacted, communication between leaders and employees goes well enough. (3) Efforts to improve with training and Competency Based Training (CBT) are expected to be able to develop expertise or skills specifically and have the aim of achieving work results based on performance targets that have been set.